Profil Self-awareness Remaja - Ruzika Hafizha (Journal of Education and Counseling (JECO), 2021)
Academic integrity is the most important thing in realizing educational goals. Every student, educator, and school staff are required to uphold the values of academic integrity. Academic integrity is a commitment to academic values that are manifested in behaviors, namely honesty, trust, justice, respect and responsibility in carrying out academic demands. Academic integrity is an academic culture that needs to be maintained. Low academic integrity leads to various academic violations such as plagiarism, data falsification, dishonesty and cheating during exams or tests. Each educational institution certainly has its own code of honor in solving problems of academic violations and maintaining the honor of their educational institution. Writing this article aims to obtain an overview of the definition of academic integrity, characteristics of academic integrity, and the factors that affect academic integrity studied from various literatures. The results of this literature review study are used to develop academic integrity theory. Keyword: Academic Integrity, Responsibility, Plagiarism Abstrak: Integritas akademik merupakan hal terpenting dalam mewujudkan tujuan pendidikan. Setiap peserta didik, pendidik, dan staf sekolah dituntut untuk menjunjung tinggi nilai-nilai integritas akademik. Integritas akademik merupakan komitmen terhadap nilai-nilai akademik yang diwujudkan dalam perilaku-perilaku yaitu kejujuran, kepercayaan, keadilan, menghargai dan tanggung jawab dalam menjalankan tuntutan akademik. integritas akademik adalah budaya akademik yang perlu dipelihara. Integritas akademik yang rendah menimbulkan berbagai pelanggaran akademik seperti plagiarisme, pemalsuan data, ketidakjujuran dan kecurangan selama ujian atau tes. Setiap lembaga pendidikan tentu memiliki kode kehormatan masing-masing dalam menyelesaikan masalah pelanggaran akademik dan mempertahankan kehormatan lembaga pendidikan mereka. Penulisan artikel ini bertujuan untuk memperoleh ikhtisar mengenai definisi integritas akademik, karakteristik integritas akademik, serta faktor-faktor yang mempengaruhi integritas akademik yang dikaji dari berbagai literature. Hasil studi literature review ini digunakan untuk pengembangan teori integritas akademik. Kata Kunci: Integritas Akademik, Tanggung Jawab, Plagiarisme